La Politique Budgétaire Comme Instrument De Stabilité Et De Sortie Des24. Crises Financières Et économiques - Omrani, Talal (جامعة الوادي- University of Eloued, 2017)
The role of the State in the economy has long been the subject of controversy among economists. According to the Liberals, the role of the State is limited to allow the market to operate, to fill some of the shortcomings, to produce certain collective equipment and especially to ensure the safety and security of goods and persons. The market naturally tending to self-regulate, in a context of free competition, should lead to an optimal allocation of resources.
مقال
Keywords: Politique budgétaire expansionniste, Contre-choc pétrolier, Politique contra-cyclique, Politique pro-cyclique, Crise financière et économique, Syndrome hollandais